2007
DOI: 10.1007/s00167-007-0416-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a contoured articular prosthetic device on tibiofemoral peak contact pressure: a biomechanical study

Abstract: Many middle-aged patients are affected by localized cartilage defects that are neither appropriate for primary, nor repeat biological repair methods, nor for conventional arthroplasty. This in vitro study aims to determine the peak contact pressure in the tibiofemoral joint with a partial femoral resurfacing device (HemiCAP ® , Arthrosurface Inc., Franklin, MA, USA). Peak contact pressure was determined in eight fresh-frozen cadaveric specimens using a Tekscan sensor placed in the medial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
54
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 32 publications
1
54
0
2
Order By: Relevance
“…Becher et al compared implantation levels of a femoral condyle HemiCAP using human cadaver specimens. 43 Th ey concluded that protruding implantation led to substantially increased peak contact pressure, as also occurred in our single protruding implantation (specimen no. 11).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Becher et al compared implantation levels of a femoral condyle HemiCAP using human cadaver specimens. 43 Th ey concluded that protruding implantation led to substantially increased peak contact pressure, as also occurred in our single protruding implantation (specimen no. 11).…”
supporting
confidence: 63%
“…In particular, the periphery of the implant cap should be recessed because "edge-loading" may result in a poor outcome. 43,222 . Th e lateral part of the implant can be considered to be crucial because it is located on the weight-bearing talar dome articulating with the tibial plafond.…”
mentioning
confidence: 99%
“…Focal resurfacing with use of a metallic cap has been shown to be a promising alternative approach with which to avoid or delay joint replacement in middle-aged and older patients [14][15][16][17][18][19] . However, recent animal studies have suggested that articular damage can be associated with these implants [20][21][22] , especially in the case of surface-proud implantation.…”
mentioning
confidence: 99%
“…Both microfracture and metal implants damage the directly articulating cartilage, and remote places in the knee, but metal implants cause less damage than the microfracture technique (Custers et al 2009b). Contact pressures on the articulating surfaces from metal implants have been studied using human cadaveric knees, showing that position of the implant significantly affects the contact pressure (Becher et al 2008(Becher et al , 2009.…”
Section: Introductionmentioning
confidence: 99%